Forest Litterfall in India: a Review and an Estimate of Litterfall Carbon Flux - Dadhwal, V. K.; Shukla, N.; Vora, A. B. (Indian Forester, 1997)
Using 44 published studies describing 64 and 75 measurements on total and leaf litterfall in Indian forest, respectively, average litterfall for major forest types was computed. This ranged from 8.5 to 4.3 t/ha/yr for total litterfall and 6.9 to 3.4 t/ha/yr for leaf litterfall. The mean litterfall was used along with remote sensing based forest type inventory by Forest Survey of India (1987 assessment, based on 1980-82 satellite data) to estimate aboveground total and leaf litterfall carbon flux of 188 Â± 24 and 152 Â± 13 Mt C/yr in forest in India.